2007
DOI: 10.1074/jbc.m702732200
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Pathways for Transfer of Acyl Groups from Mitochondria to the Cytosol to Form Short Chain Acyl-CoAs in the Pancreatic Beta Cell

Abstract: The mitochondria of pancreatic beta cells are believed to convert insulin secretagogues into products that are translocated to the cytosol where they participate in insulin secretion. We studied the hypothesis that short chain acyl-CoA (SC-CoAs) might be some of these products by discerning the pathways of SC-CoA formation in beta cells. Insulin secretagogues acutely stimulated 1.5-5-fold increases in acetoacetyl-CoA, succinyl-CoA, malonyl-CoA, hydroxymethylglutaryl-CoA (HMG-CoA), and acetyl-CoA in INS-1 832/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
107
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 51 publications
9
107
0
Order By: Relevance
“…INS-1 832/13 cells (passage number 10-15) were cultivated as monolayers on 150 mm tissue culture plates in INS-1 medium (RPMI tissue culture medium (contains 11.1 mM glucose) supplemented with 10% fetal bovine serum, 10 mM Hepes buffer, 1 mM pyruvate and 50 μM β-mercaptoethanol) [23] and penicillin (100 units/ml) and gentamycin (100 μg/ml) [12,13]. Twenty-two hours before experiments were performed the glucose concentration in the tissue culture medium was reduced to 5 mM.…”
Section: Measurement Of 14 C Incorporation From Glucosementioning
confidence: 99%
See 4 more Smart Citations
“…INS-1 832/13 cells (passage number 10-15) were cultivated as monolayers on 150 mm tissue culture plates in INS-1 medium (RPMI tissue culture medium (contains 11.1 mM glucose) supplemented with 10% fetal bovine serum, 10 mM Hepes buffer, 1 mM pyruvate and 50 μM β-mercaptoethanol) [23] and penicillin (100 units/ml) and gentamycin (100 μg/ml) [12,13]. Twenty-two hours before experiments were performed the glucose concentration in the tissue culture medium was reduced to 5 mM.…”
Section: Measurement Of 14 C Incorporation From Glucosementioning
confidence: 99%
“…The rate of pyruvate carboxylation correlates with the glucose concentration applied to pancreatic islets and thus is correlated with the rate of insulin secretion [5]. 13 C-NMR isoprotomer studies of glucose metabolism in clonal cell lines have also shown a correlation between insulin secretion and pyruvate flux through the pyruvate carboxylase reaction [8,9]. The purpose of anaplerosis in the beta cell is different from that in many other tissues which possess a high level of pyruvate carboxylase.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations